2000
DOI: 10.1103/physreve.61.468
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of flames in wide tubes: Stability limits of curved stationary flames

Abstract: Flame dynamics in wide tubes with ideally adiabatical and slip walls is studied by means of direct numerical simulations of the complete set of hydrodynamical equations including thermal conduction, fuel diffusion, viscosity, and chemical kinetics. Stability limits of curved stationary flames in wide tubes and the hydrodynamic instability of these flames (the secondary Darrieus-Landau instability) are investigated. The stability limits found in the present numerical simulations are in a very good agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…Asymmetric cells of this type are seen for one case of the solution of the MichelsonSivashinsky equation (Michelson and Sivashinsky 1977), but unlike here, it was later found that this was just a transitory stage and eventually the solution evolved to a single symmetric cell across the domain (Gutman & Sivashinsky 1990). However, for a domain width similar to the one used here (in terms of λ m ) and perturbation wavelength corresponding to our λ = 24 ∼ 2λ m case, Travnikov et al (2000) also found in their Le = 1 calculations that the cell evolved from a half a cell across the domain to a single asymmetric cell. The mechanism in their purely hydrodynamic case appears to be different, in that there is no temperature overshoot, and the new cusp forms in the interior of the domain not at the symmetry line corresponding to the original crest.…”
Section: Nonlinear Evolution and Stationary Statesmentioning
confidence: 43%
See 4 more Smart Citations
“…Asymmetric cells of this type are seen for one case of the solution of the MichelsonSivashinsky equation (Michelson and Sivashinsky 1977), but unlike here, it was later found that this was just a transitory stage and eventually the solution evolved to a single symmetric cell across the domain (Gutman & Sivashinsky 1990). However, for a domain width similar to the one used here (in terms of λ m ) and perturbation wavelength corresponding to our λ = 24 ∼ 2λ m case, Travnikov et al (2000) also found in their Le = 1 calculations that the cell evolved from a half a cell across the domain to a single asymmetric cell. The mechanism in their purely hydrodynamic case appears to be different, in that there is no temperature overshoot, and the new cusp forms in the interior of the domain not at the symmetry line corresponding to the original crest.…”
Section: Nonlinear Evolution and Stationary Statesmentioning
confidence: 43%
“…The first scheme is an explicit secondorder in time and space Godunov type solver (cf. Kadowaki (1997Kadowaki ( ,1999Kadowaki ( ,2000 and Travnikov et al (2000)). In this case, the hyperbolic fluxes are evaluated using a linearized Riemann solver while the diffusive terms are approximated by central differences.…”
Section: Numerical Methods and Initial And Boundary Conditionsmentioning
confidence: 99%
See 3 more Smart Citations